2021
DOI: 10.1051/0004-6361/202141248
|View full text |Cite
|
Sign up to set email alerts
|

Disks in close binary stars

Abstract: Context. Close binaries (abin ≤ 20 au) are known to harbor planets, yet planet formation is unlikely to succeed in such systems. Studying the dynamics of disks in close binaries can help to understand how those planets could have formed. Aims. We study the impact that numerical and physical parameters have on the dynamics of disks in close binaries. We use the γ-Cephei system as an example and focus on disk quantities such as disk eccentricity and the precession rate as indicators for the dynamical state of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…During the pericenter passage of the secondary star of eccentric binaries, strong spiral arms develop in the disk of both the primary and secondary star. This has been shown by hydrodynamical numerical simulations of close binary stars [91,[96][97][98][99][100][101] taking as test bench the γ Cep and α Cen systems. In Fig.…”
Section: Outer Stellar Companionsmentioning
confidence: 75%
“…During the pericenter passage of the secondary star of eccentric binaries, strong spiral arms develop in the disk of both the primary and secondary star. This has been shown by hydrodynamical numerical simulations of close binary stars [91,[96][97][98][99][100][101] taking as test bench the γ Cep and α Cen systems. In Fig.…”
Section: Outer Stellar Companionsmentioning
confidence: 75%
“…For outward drift to be possible, depending on the temperature the eccentricity must be increasing outwards and 0.1. Simulations of disks in binary systems often find a region of the disk with these properties (e.g., Marzari et al 2009;Martin et al 2020;Jordan et al 2021), however the details vary substantially from one work to another. Jordan et al (2021) ran a series of two-dimensional radiative hydrodynamic simulations using the FARGO code.…”
Section: Effect Of Disk Parametersmentioning
confidence: 99%
“…Simulations of disks in binary systems often find a region of the disk with these properties (e.g., Marzari et al 2009;Martin et al 2020;Jordan et al 2021), however the details vary substantially from one work to another. Jordan et al (2021) ran a series of two-dimensional radiative hydrodynamic simulations using the FARGO code. They found that the eccentricity profile was dramatically affected by choices regarding the simulation domain, the boundary condition at the inner edge of the disk, the treatment of thermodynamics, and the numerical resolution.…”
Section: Effect Of Disk Parametersmentioning
confidence: 99%
“…Later [97] and [98,99] argued that eccentricity was overestimated, and a proper treatment of viscous heating and radiative cooling, as well as the inclusion of disc self-gravity, implies lower disc eccentricities. However, most recently [100] showed that these works may have suffered from too low numerical resolution, and that more realistic viscosities lead to e ≈ 0.2, leaving this problem open.…”
Section: Can Disc Models Explain the Observed Binary Planets?mentioning
confidence: 99%